2016
DOI: 10.1016/j.renene.2015.06.072
|View full text |Cite
|
Sign up to set email alerts
|

Carbonisation of wood residue into charcoal during low temperature process

Abstract: a b s t r a c tTorrefaction process of wood residue was tested at 230 C, 260 C and 290 C temperatures under 0.5 h, 1.0 h and 1.5 h time in an electrical furnace. The studied material was characterised in terms of its proximate and ultimate analysis. HHV before and after torrefaction was calculated. The behaviour of raw and torrefied biomass was moreover investigated by thermogravimetric analysis, (TG, DTG) and the structural shrinkage was studied by SEM, too. It was found that the most efficient carbonising pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…4 shows that the elemental composition of torrefied food waste that moves Van Krevelen plot of raw and torrefied food waste samples at various temperature, residence time, particle size towards coal, with the best result is obtained from torrefaction of food waste at 320 °C, 60 min and 0.5 mm. The results are in accord with numerous literature that has reported that torrefied biomass possesses characteristics close to or similar to the coal [18][19][20][21].…”
Section: Ultimate Analysissupporting
confidence: 92%
“…4 shows that the elemental composition of torrefied food waste that moves Van Krevelen plot of raw and torrefied food waste samples at various temperature, residence time, particle size towards coal, with the best result is obtained from torrefaction of food waste at 320 °C, 60 min and 0.5 mm. The results are in accord with numerous literature that has reported that torrefied biomass possesses characteristics close to or similar to the coal [18][19][20][21].…”
Section: Ultimate Analysissupporting
confidence: 92%
“…[11,19] Advantages  Could be applied to a wide variety of feedstock (softwood, hardwood, herbaceous, waste) Compared with traditional pellets, torrefied pellets have:  Higher bulk and energy density;  Higher mechanical strength and lower dust formation;  Better hydrophobicity and reduced biological degradation, resulting in no need for covering and for expensive storage solutions;  Homogeneity and grindability properties similar to coal, therefore no need of dedicated milling and feeding infrastructure at coal power plants. [11][12][13][14][15][16][17][18] Issues Torrefaction in combination with pelletization  New and emerging technology, with limited industrial applications to date and high capital costs.  Limited data on process and pellet properties are available from a few pilot plants.…”
Section: Advantagesmentioning
confidence: 99%
“…28,29 Oxygen was removed via reactions releasing it as water vapour, CO and CO 2 . 30 Decreasing hydrogen contents in torrefied wood resulted from the removal of hydroxyl groups in the form of water.…”
Section: Elemental Analysismentioning
confidence: 99%